2019
DOI: 10.1371/journal.pone.0214842
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy of transvaginal sonography versus magnetic resonance imaging in the diagnosis of rectosigmoid endometriosis: Systematic review and meta-analysis

Abstract: Introduction Intestinal endometriosis is considered the most severe form of deep endometriosis, the rectosigmoid being involved in about 90% of cases of bowel infiltration. Transvaginal sonography (TVS) and magnetic resonance imaging (MRI) have been used for noninvasive diagnosis and preoperative mapping of rectosigmoid endometriosis (RE), but no consensus has been reached so far regarding which method is the most accurate in this setting. Objective We aimed at performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
2
31
2
3
Order By: Relevance
“…TVUS had a pooled sensitivity and specificity of 76 and 94% with high diagnostic accuracy (AUC =0.92). These findings are in agreement with earlier reviews on the diagnostic accuracy of TVUS, which also indicated the high specificity and high diagnostic accuracy of this technique (AUC >0.90) ( 11 , 46-48 ). However, compared with the previous reviews, a greater number of studies were included in the present analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TVUS had a pooled sensitivity and specificity of 76 and 94% with high diagnostic accuracy (AUC =0.92). These findings are in agreement with earlier reviews on the diagnostic accuracy of TVUS, which also indicated the high specificity and high diagnostic accuracy of this technique (AUC >0.90) ( 11 , 46-48 ). However, compared with the previous reviews, a greater number of studies were included in the present analysis.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, no previous reviews have compared the accuracy of TRUS and TVUS for the diagnosis of DIE. The present study revealed MRI to have lower sensitivity (82%) and specificity (87%) for diagnosis of DIE when compared with the previous reviews of Moura et al (46) and Nisenblat et al (11). Their studies demonstrated ~90% sensitivity and specificity of MRI for diagnosis of DIE.…”
Section: Discussioncontrasting
confidence: 80%
“…The specificity of transvaginal USG ranges from 66.7% to 100%, while that of NMR ranges from 50% to 100%. 13 In the present study, 3D anorectal USG had almost perfect agreement, according to the kappa coefficient, when comparing lesions that invade the muscularis propria; however, such expressive agreement values were not observed in patients without lesions or those with lesions in the perirectal fat. In this service, 3D anorectal USG showed a significant correlation in the diagnosis of deep intestinal pelvic endometriosis and involvement of the muscularis propria.…”
Section: Discussioncontrasting
confidence: 42%
“…10 Some studies indicate pelvic ultrasound as a first-line diagnostic test, leaving NMR and endoscopic USG of the rectosigmoid as second and third lines of diagnosis, 12 although some systematic reviews demonstrated that both NMR and transvaginal pelvic USG have similar sensitivity and specificity in the diagnosis of deep endometriosis. 13 Some studies 14 compared the accuracy of two-dimensional vs. three-dimensional USG diagnosis and showed no significant difference between positive and negative predictive values; however, this comparison was made with the use of transvaginal USG rather than rectal USG. 12 Surgical treatment of deep endometriosis involves surgical techniques known as muscle layer dissection (shaving), disc resection, and intestinal resection (segmental or patch).…”
Section: Discussionmentioning
confidence: 99%
“…18 Another systematic review compared the accuracy of MRI with TVS for diagnosis of rectosigmoid endometriosis and reported that both of these techniques are equally effective for diagnosing endometriosis. 19 Although laparoscopy is the gold standard for the diagnosis of endometriosis, however, efficacy of laparoscopy is reduced in patients with mild or minimal disease. It is also difficult to diagnose lesions which are atypical in appearance.…”
Section: Discussionmentioning
confidence: 99%